(untitled) (Journal of Educational Sciences, 2016)
The article highlights the ways, methods, types of tests of physical fitness, including the results of power abilities development of studying young people. On the conclusion of the author the youth of today in most is physically underdeveloped, has the skills of a sedentary lifestyle. This problem is concerned with teachers, doctors and other professionals of this sphere. The article describes the results of an experimental work for development of power qualities of teenagers and young people. Therefore, these results represent ways, methods and tests of power abilities of learning young people. The development of power qualities is possible in young age with the help of athletic gymnastics.